Patterns of phytoplankton blooms in San Pedro Bay, Leyte, Philippines (2012-2018) - Gonzales, Niña Lyn C. (2018)
This research aimed to investigate the patterns of phytoplankton blooms on monthly monitoring and a consolidated data set. Secondary data from 2012 to 2016 were gathered. The qualitative data from October 2017- January 2018 were obtained by collecting samples using the 1 m long conical plankton net (20um mesh size and aperture diameter of 30 cm) and were preserved. On the other hand, quantitative samples for phytoplankton were gathered using a bucket and were also preserved. Physicochemical parameters including depth, light intensity temperature, salinity, pH, turbidity, chlorophyll-a, current speed and nutrient concentration (nitrate and phosphate) were also recorded. During the sampling period from October 2017-January 2018, the highest total cell density of Skeletonema was recorded in January 2018 (16.96 x 10 raised to 4 cells/L). On the other hand, Dinophysis was observed to have a high cell density during January 2012 (0.40 x 10 raised to the power of 4 cells/L), August 2012 (0.39 x 10 raised to the power of 4 cells/L) and November 2015 (0.28 x 10 raised to the power of 4 cells/L). Based from the consolidated data gathered, high cell densities of phytoplankton were likely to occur around the months of December and January 2018 at 6.16 plus/minus 7.08 ug/L while the lowest was during October 2017 at 0.01 plus/minus 0.06 ug/L. The highest turbidity recorded was also during December 2017 (7.79 plus/minus 5.38 NTU), while the lowest turbidity value was observed during December 2012 (0.48 plus/minus 0.04 NTU). The current physicochemical parameter values during October 2017-January 2018 were also written in the table for comparison purposes.